Pandemic Impact on Migrants, Immigrants and Reverse Migrants in India. Implications for Immediate Policy Interventions - R. Pazhanisamy (Department of Humanities and Social Sciences, FET, Jain University Global campus, 2020)
The present Covid -19 pandemic has taken away many millions of lives across the countries and negatively affect the lifestyles of crores of households and the migrant populations are the immediate victims of such disaster. This policy brief trace and reveals the extent of migrants population in India and discover the lock down caused socio economic impact of covid-19 and highlight the gap where the state intervention is immediately warranted.
Additional information: Disclaimer: The views appeared in the papers are of the author/s only. In no way it reflect the views of the institutions for the which the author/s belongs to.
Keywords: J21; J46; J58; J68; J61; J82; O15; 330; Migration; Immigration; Impact of Pandemic; Covid-19 and Migration; Reverse Migration; labor issues